The Development of Identity Coherence among Ethnic-Racially Minoritized Youth: Considering the Roles of Ethnic-Racial Discrimination and Identity Exploration - Park, Yerin. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Child Development.; Advisor: Sara Johnson.; Committee: Richard Lerner, Theo Klimstra, and Linda Juang.; Keyword: Developmental psychology.